2016
DOI: 10.1039/c6ce01196a
|View full text |Cite
|
Sign up to set email alerts
|

Study of the morphological evolution of vanadium pentoxide nanostructures under hydrothermal conditions

Abstract: A detailed study on the morphological evolution of one-dimensional (1D) vanadium pentoxide (V 2 O 5 ) nanostructures was performed. Small-angle X-ray scattering (SAXS) and electron microcopy techniques were used for the analyses of the influence of synthesis parameters on a hydrothermal synthesis method of V 2 O 5 nanostructures based on the degradation of a peroxocomplex precursor. A mechanism that explains the morphological evolution under different experimental conditions is proposed and the role of the deh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
(113 reference statements)
1
7
0
Order By: Relevance
“…It was also observed that the BV-25 suspension maintained its yellow color (the same characteristic color of the vanadium peroxocomplex) even after synthesis and centrifugation, indicating that 5 the V 5+ ions were not completely released from the complex, and the BiVO 4 formation was incomplete. 36 Conversely, the XRD patterns for the samples synthesized by hydrothermal treatment under temperatures ranging from 80 °C to 160 °C (Fig. 1) were similar and presented well-defined peaks, which could be indexed 10 as the pure monoclinic BiVO 4 crystalline phase (JCPDS -83-1699).…”
Section: Characterization Of the As-synthesized Samplesmentioning
confidence: 88%
See 1 more Smart Citation
“…It was also observed that the BV-25 suspension maintained its yellow color (the same characteristic color of the vanadium peroxocomplex) even after synthesis and centrifugation, indicating that 5 the V 5+ ions were not completely released from the complex, and the BiVO 4 formation was incomplete. 36 Conversely, the XRD patterns for the samples synthesized by hydrothermal treatment under temperatures ranging from 80 °C to 160 °C (Fig. 1) were similar and presented well-defined peaks, which could be indexed 10 as the pure monoclinic BiVO 4 crystalline phase (JCPDS -83-1699).…”
Section: Characterization Of the As-synthesized Samplesmentioning
confidence: 88%
“…This is possibly explained by the fact that H 2 O 2 reacts with V 5+ ions forming the stable peroxo-complex under environmental conditions during relative short periods of time. 36 Thus, the subsequent hydrothermal treatment, even when performed at 15 80 °C, provides sufficient energy to degrade the vanadium peroxo-complex, making all V 5+ ions free to form the BiVO 4 structure. Thus, XRD results clearly showed that the hydrothermal treatment has a fundamental role in the synthesis of pure monoclinic BiVO 4 .…”
Section: Characterization Of the As-synthesized Samplesmentioning
confidence: 99%
“…Some previous reports have shown the oriented attachment of nanobrils on the formation of vanadate nanobers by adding orthorhombic V 2 O 5 powder to a H 2 O 2 aqueous solution 21,22 or pouring melted orthorhombic V 2 O 5 into water. 23 The former reports showed that side-by-side attachment of nano-brils occurs on the growth process of V 2 O 5 $nH 2 O under a hydrothermal condition.…”
Section: Morphological Evolution Of V 2 O 5 $Nh 2 O Gel Skeletonsmentioning
confidence: 99%
“…In previous works, two growing mechanisms were proposed: one is growth by the addition of VO 2+ cations, 16 and the other is growth by the selfassembly of small threads. 13,[21][22][23] In the process using alkoxide, the morphological evolution of V 2 O 5 $nH 2 O xerogels has not been traced due to a high reactivity of the vanadium sources.…”
Section: Introductionmentioning
confidence: 99%
“…Among such routes, the conventional hydrothermal treatment has several advantages related to its technical convenience in obtaining well-structured ZnO crystals grown directly onto a substrate by means of relatively low-temperature treatment [30][31][32][33][34][35]. The morphological and surface properties of these nanostructures can be controlled by the optimization of some synthesis parameters, such as precursor concentration, source (distinct counterions), solvent, temperature and reaction time, among others [29,30,33,[35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%